(untitled) (World Bulletin of Public Health, 2022)
In type 2 diabetes mellitus (T2DM) patients, Vitamin D deficiency, increased C-reactive protein indices and abnormal lipid profile have a high association with cardiovascular(CDV) complications. This research was done to search relationship between glycemic control in T2DM patients and some parameters, included vitamin D, C-reactive protein (CRP), some complete blood count (CBC) and lipid status